Pioneering a Novel Cauterising Alum and Silver Nitrate (CAS) Approach for Infantile Perianal Fistulas: A Retrospective Cohort Study - Shikha, Anas; Ahmed, Mashal; Zaghloul, Zahraa; Eltaeb, Khalid; Wong, Janice (Journal of Neonatal Surgery, 2025)
Background: Perianal fistulas in infants pose significant management challenges, often necessitating a difficult choice between prolonged conservative observation and invasive surgical interventions. These treatment options are typically associated with prolonged discomfort or complications, highlighting the need for a more efficient alternative to address current challenges. Aim and Method: This retrospective cohort study involved infants under 18 months treated for perianal fistulas, either as complications of perianal abscesses or as primary perianal fistulation, at the only paediatric surgical unit in X country from 1st August 2019 to 31st July 2023. The Cauterising Alum and Silver Nitrate (CAS) treatment involved flushing the fistula with alum and silver nitrate solutions, administered at two-week intervals until discharge ceased. Results: A total of 21 fistulas in 18 patients were treated using CAS. The majority of patients achieved cessation of discharge within one month (90%), with only one case of fistula recurrence requiring an additional application of CAS and two other cases of recurrent abscess treated conservatively with drainage and antibiotics, without further recurrence. Follow-up at a mean of 15.5 months after symptom resolution revealed no adverse effects, although 24% developed simple granulomas requiring topical management. Conclusion: The CAS treatment approach offers a promising, minimally invasive alternative for managing perianal fistulas in infants, achieving rapid resolution and avoiding surgery. Despite a small sample size and single-centre scope, the consistent protocol provides valuable insights into this effective outpatient option for infant care